Patient-assisted compression helps for image quality reduction dose and improves patient experience in mammography. (November 2018) - Balleyguier, Corinne; Cousin, Morgane; Dunant, Ariane; Attard, Marie; Delaloge, Suzette; Arfi-Rouche, Julia
Abstract: We evaluated the impact of patient-assisted compression (PAC) on image quality, dose, workflow and patient experience of mammography. Patients aged 40–90 years coming for bilateral mammography were included prospectively in the study. After positioning each breast, the technologist performed the compression and exposure of the first breast, initiated the compression of the other until 3 daN and then let the patient complete the compression using a remote control device. Image quality, compression force, breast thickness, average glandular dose and pain value for each breast were assessed for PAC and technologist compression (TC). The compression level was significantly higher with PAC than TC for both craniocaudal (CC; median difference 2.0 daN, p < 0.0001) and mediolateral oblique (MLO) views (median difference 1.5 daN, p < 0.0001). Breast thickness was reduced with PAC (CC, median difference −1.90 cm, p = 0.02), as well as glandular dose (CC, median difference −0.03, p = 0.02). The image quality was rated equivalent for both modes in 85% (85/100) of cases, superior for PAC in 10% (10/100) of cases and inferior in 5% (5/100) of cases. There was no significant difference in discomfort or pain felt between PAC and TC modes. Seventy-four percent of patients reported that the self-compressing device would facilitate their reattendance. PAC may be a suitable technique for mammography examinations, providing an equivalent image quality to TC. Moreover, as the breast compression level is increased, PAC may help reduce breast thickness, hence glandular dose. The fact that patients have control over the procedure may change their perception of mammography and improve uptake and compliance. Highlights: Patient-assisted compression doesn't impair mammogram quality. Patient-assisted compression increases breast compression and lower radiation dose. Anxiety linked to mammography may be reduced by this new technic.